Role of the transcriptional regulator FHL2: identification of fish target genes and regulatory mechanisms - Rafael, Marta S. (2014)
Tese de dout., Bioquímica (Biologia Celular e Molecular), Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2011